Flood Analysis: Case Study of Terusan Pemuda Road - Nasrudin, Jujun; Faisal, Faisal; Arbiansyah , Muhammad Nabil; Nurdiyanto, Nurdiyanto (Indonesian Journal of Advanced Research, 2025)
This study analyzes flood characteristics on Jalan Terusan Pemuda, Kesambi District, Cirebon City, driven by climate change and urbanization. Methods include rainfall analysis using the Thiessen Polygon method, rainfall frequency analysis with the Gumbel method, and drainage capacity evaluation using the Manning equation. Maximum daily rainfall data from 2015–2024 shows that the Penggung station contributed the most rainfall despite its smaller coverage area. The design rainfall for 2-, 5-, and 10-year return periods is 95.58 mm, 130.62 mm, and 153.83 mm, respectively. Drainage evaluation revealed that channels P5 and P9 are overloaded, while P1 and P10 are non-functional due to sedimentation and waste. Recommendations include channel normalization, construction of interceptor systems, implementation of Low Impact Development (LID) concepts, public education, and improved inter-agency coordination.